The Cold War and The Retention of British Rule in Cyprus, 1945-1947 - Hussain, Norasmahani (European Publisher, 2019)
The Mediterranean island of Cyprus was proclaimed as a Crown colony of Britain in 1925. Cyprus’ inhabitants, particularly the Greek Cypriots, strongly asked for enosis (union) with Greece; hence they revolted against British rule in Cyprus. This paper will detail Britain’s decision with regards to the retention of its rule in Cyprus, despite the Greek islanders’ pressure that Cyprus be handed back to Greece. The strategic geographical location of Cyprus, being near to British route to the Middle East and the Eastern Empire, is a notable issue reflected in existing literature. A number of historians agreed that this was the obvious justification for Britain to decline the Greek Cypriots’ demand for enosis and thus maintaining British rule in Cyprus. The prime objective of this paper is to identify the reason for Britain to stay in Cyprus from a point of view that has acquired slight scholarly consideration. This paper has concentrated on the viewpoint of British Foreign Secretary Ernest Bevin and his Foreign Office through the perusal of archival or primary records such as Bevin’s Private Papers (FO 800), the Cabinet Office Papers (CAB), the Foreign Office Papers (FO 371), the Defence Ministry Papers (DEFE) and the House of Commons Parliamentary Debate (HANSARD). The scrutiny of these records has discovered that Bevin, Head of the Foreign Office, wanted to stay in Cyprus due to the Cold War tension in Greece. It seemed likely that Cyprus would also turn communist if it was ceded to Greece during this crucial time.